COMPARATIVE COMPLEXATION BEHAVIOR OF THE RARE EARTHS - Byrne R.H.; Biqiong L. (My University, 1995)
Linear free energy relationships (LFERs) have been used to assess the general character of rare earth element (REE) solution complexation. These analyses demonstrate that the coherence of interelement complexation behavior changes substantially across the fifteen-member series of REEs. The most coherent interelement relationships with a single rare earth reference element and the remaining rare earths as a group are obtained by referencing rare earth complexation behavior to Dy. The least coherent relationships are obtained using Pr or Nd as reference elements. Across the rare earth series of elements a light rare earth pattern of complexation behavior (La-Eu) and a heavy rare earth pattern of complexation behavior (Tb-Lu) is observed. At the junction of these light (LREE) and heavy (HREE) rare earth element series, Gd appears to behave as a HREE for weak (outersphere) complexation and as a LREE for strong (innersphere) complexation. Due to the unique position of Gd among two trends of complexation behavior, the solution chemistry of Gd may appear anomalous with respect to the complexation behavior of its immediate neighbors. Other than that observed for Gd, our work provides no evidence for substantial ''breaks'', junction points, or apparent anomalies in the average behavior of aqueous REE stability constants. The quantitative LFER results obtained in this work can be used to examine the complexation characteristics of individual ligands in the context of typical (average) REE complexation behavior. Such examinations reveal that substantial deviations from ''average'' behavior are common. This observation demonstrates, in a geochemical context, that detailed observation of REE complexation by organic ligands on particle surfaces is required to understand REE behavior in the organic-rich marine environment.